The case for certificate automation. Issue 9 (September 2021) - Hojjati, Avesta
Abstract : IT departments spend too much time on repetitive, manual tasks that eat up resources that could be spent on strategic initiatives. 1 And companies that are applying automation are realising benefits beyond just the time saved. Automation is transforming businesses and positioning them for competitive advantage.